Molecular Analysis of Cry1Ab-Cry1Ac Gene Fusion in Transgenic Sugarcane Resistant to Shoot Borer Scircophaga excerptalis (Lepidoptera: Pyralidae) and Stem Borer Chilo sacchariphagus (Lepidoptera: Pyralidae) - Armita, Dea; Meryandini, Anja; Suharsono; Koerniati, Sri (Bogor Agricultural University, Indonesia, 2024)
Sugarcane (Saccharum officinarum) is a plant with high economic value because it can produce sugar. Shoot borer Scircophaga excerptalis (Lepidoptera: Pyralidae) and stem borer Chilo sacchariphagus (Lepidoptera: Pyralidae) attacks are one of the issues that limit sugarcane productivity. Establishing transgenic sugarcane is one of the most efficient ways to prevent borer damage. Previously, Cry1Ab and Cry1Ac genes were successfully used to create transgenic sugarcane plants. This study aimed to detect the presence of transgenes and analyze the expression level of the Cry1Ab-Cry1Ac gene fusion in transgenic sugarcane using RT-PCR. The methods used in this study are transgene detection with PCR and gene expression analysis in normalized expression (2-ΔΔCq) with RT-PCR. The Cry1Ab-Cry1Ac gene has been integrated into all lines with varied expression levels. In 311 GV and 333 GV lines, the Cry1Ab-Cry1Ac gene was expressed in the leaf but not in the stem. Shoot and stem borer attack percentage values showed that all lines were lower than the control, with 222 EH as the lowest and 311 GV as the highest. Leaf and stem borer attack levels were compared to gene expression values of Cry1Ab-Cry1Ac. Results may indicate that the 222 EH line was resistant, but the 311 GV and 333 GV lines were not.